Disease burden and trends of lung cancer attributable to nickel among Chinese and global population: a cross-sectional study - Lu, Huaye; Han, Lei; Wu, Peihong; Liu, Xin; Jiang, Qingtao (Frontiers in Medicine, 2024)
BackgroundNickel is a well-established carcinogen, and China stands as a significant producer of nickel compounds. Nickel-associated lung cancer is increasingly acknowledged as a pressing public health concern. This study presents a comprehensive analysis at temporal, spatial, and population levels utilizing the most recent data from GBD 2019 to estimate the disease burden of nickel-associated lung cancer from 1990 to 2019, and make predictions to 2035.MethodsWe delineated data on nickel-associated lung cancer concerning mortality, disability-adjusted life years (DALY), and age-standardized rates (ASRs) over a 30-year period based on the global burden of disease (GBD) 2019. Joinpoint regression analysis was utilized to identify temporal changes and to estimate the annual percentage change (APC) as well as the average annual percentage change (AAPC) for each trend segment. The Nordpred model was employed to elaborate on ASRs trends from 1990 to 2019, along with projections for the subsequent 15 years.ResultsIn both China and globally, the mortality rate from nickel-associated lung cancer and the associated DALYs have increased by 145.8, 77.8, 120.2, and 64.6%, respectively. ASRs within Chinese and global populations exhibit a pattern characterized by an initial increase followed by a decrease as age progresses, with males higher than females. The trend for DALY indicates an initial rise followed by a decline, peaking in the year 2027.ConclusionThe age structure of nickel-associated lung cancer patients shows an aging trend, and the ASDR in the Chinese population indicates a potential upward trend when projecting the disease burden of nickel-associated lung cancer over the next 15 years. We should place greater emphasis on the implementation of preventive strategies and the enhancement of the quality of life for current sufferers.